2018
DOI: 10.1016/j.schres.2017.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance of accelerated aging in schizophrenia?: Clinical and biological characterization of an exceptionally high functioning individual

Abstract: Although speculative, results suggest a possible model in which superior working memory permits a person to be aware of the potentially psychotic nature of a thought or perception, and adjust response accordingly. Compensatory overactivity of brain regions during affective processing may also reflect heightened meta-awareness in emotional situations. Biomarker levels raise the possibility that IP partially avoided the accelerated biological aging associated with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In a case-control study involving high-functioning schizophrenia patients and healthy subjects no behavioral group differences were found during facial emotion perception (Karpouzian et al, 2017). Another study (Palmer et al, 2018) using an affective face matching task (Hariri et al, 2000) in order to investigate one highfunctioning schizophrenia patient showed that this patient performed better than other non-high-functioning patients with schizophrenia and similar to a non-psychiatric control group. It is important to emphasize that deriving conclusions from a study investigating only one subject, thus not having a basis for generalization, remains highly speculative.…”
Section: Discussionmentioning
confidence: 97%
“…In a case-control study involving high-functioning schizophrenia patients and healthy subjects no behavioral group differences were found during facial emotion perception (Karpouzian et al, 2017). Another study (Palmer et al, 2018) using an affective face matching task (Hariri et al, 2000) in order to investigate one highfunctioning schizophrenia patient showed that this patient performed better than other non-high-functioning patients with schizophrenia and similar to a non-psychiatric control group. It is important to emphasize that deriving conclusions from a study investigating only one subject, thus not having a basis for generalization, remains highly speculative.…”
Section: Discussionmentioning
confidence: 97%
“…Younger adults with SMI are prone to diseases associated with aging (Czepielewski et al, 2013;Hennekens et al, 2005;Soreca et al, 2008) and have twice the risk of dying from cardiovascular and gastrointestinal diseases compared to the general population (Saha et al, 2007). Physiological changes seen throughout the body with normal aging occur at earlier ages, including chronic inflammation and oxidative stress, which has led to the theoretical framework of SMI as disorders of accelerated biological aging (Jeste et al, 2011;Kirkpatrick et al, 2008;Nguyen et al, 2018a;Palmer et al, 2018;Rizzo et al, 2014). Given that lifespans are generally increasing for the general population (Christensen et al, 2009), while the mortality gap for schizophrenia is growing (Lee et al, 2018), understanding the mechanisms of potential accelerated aging in SMI is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…The final article by Palmer et al (2018) looks at accelerated biological aging in schizophrenia from a markedly different anglehow a person with this illness can possibly avoid accelerated aging. The authors utilize a case-study approach to closely examine the clinical and biological characteristics of an exceptionally highfunctioning woman with schizophrenia who is entering late life, in comparison with demographically similar typically-functioning women with schizophrenia and with non-psychiatric comparison (NC) women.…”
mentioning
confidence: 99%